PHOTOIONIZATION OF THE OUTER SHELLS OF RADON AND RADIUM - RELATIVISTIC RANDOM-PHASE APPROXIMATION FOR HIGH-Z ATOMS - (:unkn) unknown (AMER PHYSICAL SOC, 1992)
Photoionization cross sections, branching ratios, and photoelectron angular distributions have been calculated for Ra (Z = 88) 7s, 6p, 6s, 5d, and 5p, and Rn (Z = 86) 6p, 6s, 5d, and 5p subshells within the framework of the relativistic random-phase approximation, including coupling between all of the relativistic channels arising from these subshells, in an effort to elucidate the interplay between relativistic and interchannel interactions at high Z where no experiments are extant. The results show that, aside from inducing structure in subshell cross sections, relativistic plus interchannel effects dominate the photo-electron angular-distribution asymmetry parameter and the branching ratio between spin-orbit doublets largely through the relativistic splitting of Cooper minima. This qualitatively confirms effects predicted by simple central-field calculations. Detailed explanations of the reasons for each of the structures are presented.
Keywords: HIGH-Z ELEMENTS; PHOTO-IONIZATION; COOPER MINIMA; ANGULAR-DISTRIBUTIONS; SUBSHELLS; SPLITTINGS; RRPA